Estrategias de mejora para los pequeños productores de café de la provincia de Lengupá en la cadena productiva. (2020)
The present work sought to create improvement strategies in the coffee production chain in the Lengupa province, which can maximize its production, through a mixed approach of descriptive and analytical scientific research, applying data collection instruments, the Interview as a qualitative instrument and the survey as a quantitative instrument, a sample population of small coffee producers in the province of Lengupá. Through the elaboration of a diagnosis and a process of characterization of incident variables, weaknesses, opportunities, strengths and threats will be established for the strategic formulation of productivity improvement scenarios. As a response to the needs of small producers, within this research is a strategic plan focused on the aspects of association, financing, technology, renovation and protection of coffee crops for small producers in the province of Lengupá.